ANALISIS PENERAPAN TAX AMNESTY (PENGAMPUNAN PAJAK) TERHADAP RASIO PAJAK SECARA NASIONAL DAN SECARA REGIONAL (KABUPATEN DAN KOTA TANGERANG) - Sapta Setia Darma; Zulva Sudarti; Maya Richmayati; Andi Hidayatul Fadlilah (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The research for the 2020/2021 academic year is aimed at the application of tax amnesty (tax forgiveness) to tax ratios nationally and at KPP Pratama Tangerang Timur, KPP Pratama Kosambi and KPP Pratama Tigaraksa (KPP Pratama in Tangerang Regency and Tangerang City). Tax Amnesty is a policy in the field of taxation set by the government with the approval of the House of Representatives, this policy provides forgiveness for mistakes that have been made by taxpayers in carrying out their tax obligations in the field of Income Tax (PPh), Value Added Tax of Goods and Services (PPN), and Luxury Goods Sales tax (PPnBM) until the 2015 Fiscal Year. The 2016 Tax Amnesty Policy, which among others aims to increase tax revenues and add to the taxation database, as well as an increase in the tax ratio, therefore, to see the results or impacts, it is necessary to assess or observe the condition of tax revenues, taxation databases and GDP (Domestic Product). Gross) before and after the effective period of the Tax Amnesty policy. This research aims to determine the growth of the tax ratio before and after the 2016 tax amnesty policy nationally and regionally and compare the results. This research method went through several stages, including collecting data on tax revenues and gross domestic product nationally in the period before and after the implementation of the 2016 tax amnesty policy and then calculating the tax ratio. Furthermore, the same steps are carried out regionally (East Tangerang KPP Pratama, Kosambi KPP Pratama and Tigaraksa KPP Pratama which are included in the Pratama KPP in Tangerang Regency and Tangerang City)). And then compare the results between national and regional to find out how the growth of the tax ratio both nationally and regionally after the tax amnesty policy